1999
DOI: 10.4269/ajtmh.1999.61.625
|View full text |Cite
|
Sign up to set email alerts
|

Houseflies: not simple mechanical vectors of enterohemorrhagic Escherichia coli O157:H7.

Abstract: Abstract. An epidemic of enterohemorrhagic colitis caused by Escherichia coli O157:H7 (EHEC-O157) occurred in a nursery school in a rural area of Japan in September 1996. The EHEC-O157 were isolated both from patients and houseflies collected at the school. The flies were suspected to be mechanical vectors of the pathogen. Feeding experiments of EHEC-O157 to houseflies showed that the ingested bacteria were harbored in the intestine of flies and continued to be excreted at least for 3 days after feeding. Scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
117
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 15 publications
11
117
0
3
Order By: Relevance
“…All detected bacteria from M. domestica in the current study are pathogenic. These findings agree with the previous reports of Alam & Zurek (2004), in which E. coli O157:H7 was detected in both farm and urban environments and Greenburg (1965), Kobayashi et al, (1999) and Moriya et al, (1999). In conclusion, we developed an easy and rapid Universal Primer-Multiplex PCR showing high specificity capable of detecting three bacteria.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…All detected bacteria from M. domestica in the current study are pathogenic. These findings agree with the previous reports of Alam & Zurek (2004), in which E. coli O157:H7 was detected in both farm and urban environments and Greenburg (1965), Kobayashi et al, (1999) and Moriya et al, (1999). In conclusion, we developed an easy and rapid Universal Primer-Multiplex PCR showing high specificity capable of detecting three bacteria.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that filth flies can disseminate viable pathogens such as Helicobacter pylori (Grubel et al, 1997), Salmonella (Greenburg 1965), and E. coli O157 (Kobayashi et al, 1999) has not yet been investigated in this study whether or not these organisms were carried externally or internally. All detected bacteria from M. domestica in the current study are pathogenic.…”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies have highlighted the efÞciency at which house ßies can acquire and disperse antibiotic resistant enterococci (Graham et al 2009, Chakrabarti et al 2010, Ahmad et al 2011. Further, the ability of various microbes to proliferate and possibly spread antibiotic resistance genes horizontally in the house ßy digestive tract underscores the potential of house ßies to amplify bacterial pathogens (Kobayashi et al 1999(Kobayashi et al , 2002Sasaki et al 2000;Petridis et al 2006;Akhtar et al 2009;McGaughey and Nayduch 2009). This current study adds to our understanding of the fate of E. faecalis in the house ßy digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is probable that the bacteria that multiplied in the crop were not only periodically transferred to the midgut but were also regurgitated and led to E. faecalis recovered in the labelum after the Þrst 24 h. Additionally, while the relative bacterial counts in the midgut and hindgut were lower at 96 h, the foregut retained a mean CFU count of 7.2 Ϯ 7.0 ϫ 10 5 , suggesting that the bacterium continued to proliferate in the crop/foregut. Kobayashi et al (1999) found the pseudotracheae of the labelum to be important for proliferation of E. coli O157: H7. Concentrations of E. faecalis in the labelum in our study were variable but did reveal a trend of higher counts during the latter part of the assay indicating that E. faecalis either multiplied on the surface of the labelum or propagated in the foregut/crop and were regurgitated during feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation